Sistem Pengawasan terhadap Perjanjian-Perjanjian terkait Pengiriman Pekerja Migran atau Tenaga Kerja Indonesia ke Luar Negeri - Yetniwati Yetniwati; Elita Rahmi; Hartati Hartati (Faculty of Law, Andalas University, 2020)
Supervision of labor in the process of sending migrant worker abroad began at the time of recruitment, registration, counseling, document management, training until departure. Related agreements in the process of sending migrant worker namely: Placement Cooperation Agreement; migrant worker Placement Agreement; and Work Agreement. All these agreements are in practice made in the form of standard agreements. Supervision of the strong party is necessary to avoid oversight in order to provide protection to the weak party. Supervision is carried out by agencies that work in synergy between the Ministry of Foreign Affairs, the Ministry of Manpower and the Regional Government, which has the authority and synergy to supervise both administrative and technical nature with integrated information systems in order to provide protection to Indonesian Migrant Workers Abroad